A bibliometric analysis of managerial finance: a retrospective. Issue 11 (7th July 2020) - Baker, H. Kent; Kumar, Satish; Pandey, Nitesh
Abstract : Purpose: Managerial finance (MF) started publication in 1975 and celebrated its 45th anniversary in 2019. The purpose of this study is to provide a bibliometric analysis of MF between 1996 and 2019. Design/methodology/approach: This study uses the Scopus database to analyze the most frequent authors in MF along with their affiliated institutions and countries. It also identifies the most often cited MF articles. This study uses bibliometric indicators to analyze productivity and stature of MF. It also uses such tools as bibliographic coupling, keyword analysis and coauthorship analysis to analyze MF. Further, the study provides a temporal analysis of MF publishing across different ownership periods. Findings: MF publishes between 60 and 70 articles each year and its number of citations steadily grows. Although contributors to the journal come from around the globe, they most often are affiliated with the United States, the United Kingdom and Greece. Temporal analysis of journal's themes reveals that it has expanded its scope from accounting research to a much wider array of finance topics. Bibliographic coupling network analysis shows that major themes published in MF involve stock markets, corporate governance, banking, financial decision-making and initial public offerings. Research limitations/implications: Due to the unavailability of bibliometric data, the analysis excludes an analysis of MF between 1975 and 1995. Originality/value: This study provides the first overview of the MF's publication and citation trends as well as its thematic structure. It also suggests future directions that the journal might take.